2018
DOI: 10.22409/engevista.v20i3.9500
|View full text |Cite
|
Sign up to set email alerts
|

EXTRATO DE ACÁCIA NEGRA (Acacia mearnsii de Wild.) NO TRATAMENTO DE EFLUENTES EMULSIONADOS: ESTUDO DAS CONCENTRAÇÕES E PARÂMETROS OPERACIONAIS

Abstract: Todos as informações e direitos sobre o presente artigo são de total e única responsabilidade do(s) autor(es). Resumo: O extrato de Acácia Negra vem sendo caracterizado como uma grande fonte de taninos e devido ao seu alto poder de clarificação é apontado como um agente coagulante no tratamento primário de efluentes industriais. Um grande problema das indústrias de extração de óleos comestíveis é a geração de efluentes oleosos, com emulsões estáveis óleo-água, que devem ser tratados antes de serem descartados,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…In addition, the pH of the water was not influenced, presenting values similar to those at the beginning of the process. Morandi and Kempka (2018) observed that the black wattle extract, rich in tannins, was efficient in clarifying oily effluents (soybean and sunflower oil), with removal of 50 % of the color using concentrations in the range of 0.5 to 1.0 wt.% of coagulant. The vegetable coagulant based on tannins, according to Beltrán-Heredia et al (2009), was effective in removing surfactants (about 70 %), such as sodium dodecyl benzenesulfonate for a dosage of 150 mg/L of coagulant.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the pH of the water was not influenced, presenting values similar to those at the beginning of the process. Morandi and Kempka (2018) observed that the black wattle extract, rich in tannins, was efficient in clarifying oily effluents (soybean and sunflower oil), with removal of 50 % of the color using concentrations in the range of 0.5 to 1.0 wt.% of coagulant. The vegetable coagulant based on tannins, according to Beltrán-Heredia et al (2009), was effective in removing surfactants (about 70 %), such as sodium dodecyl benzenesulfonate for a dosage of 150 mg/L of coagulant.…”
Section: Introductionmentioning
confidence: 99%